ANALISIS KESADARAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA SAMSAT KOTA BATAM - Wilda Rahmadani; Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2022)
This research was conducted to determine the effect of taxpayer awareness and tax sanctions on taxpayer compliance at the Batam City SAMSAT. The population in this study amounted to 227,484 vehicles registered with the SAMSAT of Batam City. The sampling technique used in this research is purposive sampling and is calculated using the Slovin formula, which is 100 respondents. The data used in this study is primary data, namely data obtained from questionnaires that have been filled out by respondents, while secondary data is data obtained from various existing sources and related agencies, such as journals, books and so on. The results of the research on the t-test show that the taxpayer awareness variable partially has a significant effect on taxpayer compliance, and the tax sanctions variable partially has a significant effect on taxpayer compliance. In the results of the coefficient of determination obtained the presentation of the independent variable to the dependent variable of 45.5% and the difference of 54.5% is influenced byother factors not examined in this study.